THE EFFECT OF COMBINATION FACTORS OF SALINITY AND TEMPERATURE ON THE GROWTH AND SURVIVAL RATE OF HARD CLAM (MERETRIX MERETRIX) JUVENILES - Thanh, Nguyen Xuan; Thung, Do Cong (Vietnam Journal of Marine Science and Technology, 2015)
This study was conducted to evaluate the effect of combination factors of salinity and temperature on the growth and survival rate of hard clam (Meretrix meretrix) juveniles. Hard clam was cultured in laboratory at three different temperatures (150C, 270C and 350C) in combination with three different salinity conditions (5‰, 20‰ and 35‰). Each experiment was carried out in triplicate and remained for one month. The results show that: At the experimental condition of 20‰ and 270C of salinity and temperature, the growth of hard clam juveniles was fastest and survival rate of hard clam juveniles was highest (86%). In the 150C - 20‰, 350C - 20‰, 270C - 5‰, 150C - 35‰, 270C - 35‰, the growth of hard clam juveniles was slower and their survival rate was lower with  61.3%, 42.6%, 39.3%, 10.7% and 60.6%, respectively. In the 150C - 5‰, 350C - 5‰ and 350C - 35‰, clam was dead all. Our findings are scientific basis for aquacultural planning, farm management. In addition, these findings will contribute to building cultural techniques of clam appropriate for each production season together with protection and development of hard clam resource.